EKSPLORASI KONSEP PELUANG PADA PERMAINAN TIGA DARA DI DESA GUNUNGSARI KECAMATAN BUMIAJI KOTA BATU - Jadidah, Nur Aulia (Program Studi Tadris Matematika Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
The purpose of this study, namely: 1) to know briefly about the game of three virgins. 2) to find out the exploration of the concept of opportunity that exists in the game of three virgins. This research is qualitative research using a descriptive approach (qualitative research). The data collection techniques in this study used interviews, field records, documentation data, and other documentation. The result of this study is that the game